2020
DOI: 10.1186/s10194-020-1074-0
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of headaches among patients with epilepsy: a systematic review and meta-analysis

Abstract: Background: Headache is the symptom of pain in the face, head or neck that causes disability in most people with medical and neurological disorders. It frequently co-occurs with most chronic diseases such as epilepsy and significantly impacts the quality of life. However, epidemiologic data from different studies showed different rates of prevalence. Therefore, we conducted this review to summarize the available epidemiologic evidence on the topic and formulate recommendations for future research and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 54 publications
6
18
1
1
Order By: Relevance
“…The estimated incidence of headache associated epilepsy is comparable to a recent metaanalysis of Duko et al [11] who reported that, prevalence of headache is high [48.4%] among patients with epilepsy, which require appropriate screening and proper treatment.…”
Section: Discussionsupporting
confidence: 68%
“…The estimated incidence of headache associated epilepsy is comparable to a recent metaanalysis of Duko et al [11] who reported that, prevalence of headache is high [48.4%] among patients with epilepsy, which require appropriate screening and proper treatment.…”
Section: Discussionsupporting
confidence: 68%
“…In a more recent adult large sample (15,133 subjects), migraine was also confirmed to be associated more likely with epilepsy (Buse et al, 2020 ). As further evidence in favor of a non-random association, a more recent systematic review (Duko et al, 2020 ), conducted on 5,564 study participants, reported a higher prevalence (48.4%, ranging from 46 to 52.2%) of headache among epileptic patients.…”
Section: Epilepsy and Migrainementioning
confidence: 99%
“…Pathogenic mechanisms of depression have been previously proposed as being implicated in the epileptogenic process through several mechanisms, which can be categorized as endocrine abnormalities, structural and functional abnormalities of cortical and subcortical structures, neurotransmitter abnormalities, and immunological abnormalities (for review, see Kanner (2012) 65 ). Likewise, migraine is a highly prevalent neurological comorbidity in PWE, affecting around 26% of patients 66 . The co‐occurrence of epilepsy and migraine has important prognostic implications, being associated with treatment failure and should influence drug choice, as some ASMs, such as topiramate and valproic acid, have for example, analgesic value 67 .…”
Section: Complexity About Diagnosis and Treatment Of Epilepsy And Ass...mentioning
confidence: 99%